Melatonin and Type 2 Diabetes Mellitus: the Role of Melatonin on Pathophysiology of the Disease and Potential Therapeutic - Ni Putu Dian Prakanita Dewi; Nadila Nadila; Andreas Galih Sidharta Sugiarto; Kelnia Mellenia; Ade Anjalita Santi Dewi (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Diabetes is a global health problem, with the latest data showing a global prevalence of 536,6 million (10,5%) people. The risk factors involved in the pathogenesis of diabetes, especially Type 2 Diabetes Mellitus (T2DM), are also varied, including a combination of risk factors such as age, obesity, sedentary lifestyle, environmental factors, and genetics. On the other hand, the complications associated with T2DM are also quite diverse, including diabetic neuropathy, retinopathy, nephropathy, and cardiovascular disease. Several theories have been proposed to explain the pathogenesis of complications in T2DM, one of which is cell damage due to oxidative stress. Melatonin is a hormone produced by the pineal gland known for its antioxidant properties, which can provide various therapeutic effects and health benefits, including in T2DM patients. Objective to explain further the bioactivity of melatonin, food sources of melatonin, and the role of melatonin in the pathophysiology of diseases related to its therapeutic potential in individuals with T2DM. This literature review selected various related scientific studies published within the last 10 (ten) years. A literature search was conducted through databases, such as PubMed and Science Direct, with the keywords